MicroRNA-125b-5p mimic inhibits acute liver failure - Dakai Yang; Qinggong Yuan; Asha Balakrishnan; Heike Bantel; Jan-Henning Klusmann; Michael P. Manns; Michael Ott; Tobias Cantz; Amar Deep Sharma (Nature Communications, 2016)
miR125b-5p has been associated with acute liver failure. Here the authors show that this miRNA targets Keap1 and activates Nrf2 to inhibit liver cell death after APAP or FAS toxicity, plus they show that a miR125b-5p mimic can inhibit ALF in mice.